Brand-new pencils, brand-new books - De Groat, Diane (HarperCollins Publishers, 2005)
Gilbert's excitement over starting first grade turns to worry that the teacher will be mean, the work too hard, and his classmates too unfriendly, but throughout the day there are pleasant surprises.